THE ALPHA RECEPTOR FOR PLATELET DERIVED GROWTH FACTOR CONFERS BONE-METASTATIC POTENTIAL TO PROSTATE CANCER CELLS BY LIGAND- AND DIMERIZATION-INDEPENDENT MECHANISMS - Russell, Mike R. (2010)
Prostate adenocarcinoma is the second leading cause of cancer death among men, due primarily to the fact that the majority of prostate cancers will eventually spread to the skeleton. Metastatic dissemination requires a complex series of coordinated events that result in cells that escape from the primary tumor into the circulation and eventually colonize a distant organ. The ability of these cells to evolve into macroscopic metastases depends strongly on their compatibility with, and ability to utilize, this new microenvironment. We previously showed that bone-metastatic prostate cancer cells exposed to human bone marrow respond by activation of cell survival pathways, such as PI3K/Akt, and that these events are mediated by the alpha-receptor for platelet-derived growth factor (PDGFRα). Our studies and others have shown that PDGFRα may be activated by mechanisms independent of PDGF ligand binding. Here we provide conclusive evidence that soluble components of human bone marrow can activate PDGFRα through a mechanism that does not require the canonical binding of PDGF ligand(s) to the receptor. In particular, we found dimerization of PDGFRα monomers is not induced by human bone marrow, but this does not prevent both receptor phosphorylation and downstream signaling from occurring. To establish the relevance of this phenomenon in vivo, we employed a PDGFRα mutant lacking the extracellular ligand-binding domain. Our studies show that this truncated PDGFRα was able to restore bone-metastatic potential of prostate cancer cells as effectively as the full-length form of the receptor.